Unholy trinity : the IMF, World Bank and WTO - Peet, Richard; Born, Beate (Kuala Lumpur : Sird ; Johannesburg : Wits University Press ; New York ; London : Zed Books, 2003)
A look at how the world's leading financial institutions - the IMF, World Bank and WTO - have been hijacked by the economic ideology of neoliberalism and the interest behind it, particularly from the 1980s onwards and in relation to their global financial, developmental and trade management roles.
1. Globalism and Neoliberalism -- 2. Bretton Woods: Emergence of a Global Economic Regime -- 3. The International Monetary Fund -- 4. The World Bank -- 5. The World Trade Organization -- 6. The Washington - Wall Street Alliance.
Includes bibliographical references (p. 227-239) and index.
Newaz
Keywords: International Monetary Fund -- History; World Bank -- History; World Trade Organization -- History; Globalization -- History; International Monetary Fund -- History; World Bank -- History; World Trade Organization -- History; International Monetary Fund; World Bank; World Trade Organisation; Neoliberalism; Globalisation; Developing countries; Bretton Woods